Peran Guru Dalam Meningkatkan Kemandirian Belajar Siswa SDN 064976 Medan - Safran Safran; Hasima Harahap; Khairun Nisa; Rahma Fadillah; Silvana Bayu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In the learning process every learner is always directed to become an independent student, and to become independent an individual must learn, so that learning independence can be achieved. This article analyzes the role of teachers in increasing students’ learning independence at SDN 064976 Medan. This research uses a qualitative method with a descriptive approach. It was collected through observation, interview, and documentation. The results of this study concluded that the role of teachers in increasing students' learning independence at SDN 064976 Medan is by carrying out their professional duties of teachers who have multiple roles contained in teaching and learning activities. The role of the teacher as a mentor must be more important, because the presence of a teacher in school is to guide students to become good adult humans who are capable, skilled, virtuous and noble.